2016
DOI: 10.1039/c6ra01190j
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogels from amphiphilic star block copolypeptides

Abstract: Star-shaped amphiphilic block copolymers form hydrogels as opposed to their linear counterparts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 45 publications
2
20
0
Order By: Relevance
“…Sharp absorbance peaks were recorded at 1770 cm −1 for the amide and carbonyl stretches of L‐alanine‐NCA, respectively. The presence of amide I and amide II stretches at 1637 and 1540 cm −1 , respectively, indicates the formation of poly(peptide) amide bonds 23–26 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sharp absorbance peaks were recorded at 1770 cm −1 for the amide and carbonyl stretches of L‐alanine‐NCA, respectively. The presence of amide I and amide II stretches at 1637 and 1540 cm −1 , respectively, indicates the formation of poly(peptide) amide bonds 23–26 …”
Section: Resultsmentioning
confidence: 99%
“…The co-occurrence of random coil, β-sheet, and β-turn configurations seems conceivable considering the complex polypeptide architecture. 24 The secondary structure of the mPEG-PA in aqueous solvent shifted from β-sheets to α-helices as the mPEG molecular weight M n increased from 2000 to 5000 and PA molecular weight M n decreased from 2500 to 1500 (Figure 4). 27 21 .…”
Section: Secondary Structures In Bcpmentioning
confidence: 99%
See 1 more Smart Citation
“…Native amino acids have been utilized as polymeric blocks in these supramolecular gelators, contributing to materials with tailored mechanical properties due to control of conformational assemblies . The physical bonding contributing to gelation usually emanates from the polypeptide chain composition via electrostatic interactions, hydrophobic interactions, hydrogen bonding, π–π stacking, and van der Waals forces . The resulting hydrogels possess relatively moderate mechanical strength in addition to unique properties as a consequence of their reversible non‐covalent bonding character.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] We and others have also found that use of multiblock and star copolymer architectures can enhance hydrogel properties in hydrophobically assembled copolypeptide systems. [16][17][18][19] However, these amphiphilic materials can be difficult to formulate, especially at higher concentrations, and the reported systems are not cell compatible. 18,20 Here, we sought to develop PIC multiblock copolypeptide hydrogels that could overcome these issues and allow the preparation of hydrogels with a broad range of tunable properties.…”
mentioning
confidence: 99%